Geographic distribution of Fishes and Other Commercial Animals of the Okhotsk and Bering Seas (Geograficheskoye Rasprostraneniye Ryb i Drugikh Promyslovykh Zhiyotnykh Okhotskogo i Berinogova Morey) - Kaye,K.; Hollingshead,K.; duncan ,J (1978)
Trans. of Trudy Instituta Okeanologii (USSR) v14 p1-120 1955, by M. Slessers.